2001
DOI: 10.1108/02656710110407091
|View full text |Cite
|
Sign up to set email alerts
|

Investigating organizational quality management maturity: an instrument validation study

Abstract: Reports an initial study to validate a brief instrument which could be useful as a tool to permit researchers to gain insight into a construct termed QM maturity – the quality of an organization’s adoption of (QM) programs. Notes that investigators have frequently confounded the length of time an organization reports that it has “been on” QM with the quality of its QM adoption. Yet it is entirely possible that an organization that reports that it has had quality programs in place for a considerable period of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…In this study, QM maturity refers, in a qualitative sense, to the degree of QM implementation in an organization. We suggest and previous research has shown (Ahire & Golhar, 1996;Flynn et al, 1994;Fok et al, 2000Patti et al, 2001;Saraph et al, 1989) that it can be measured by examining the perceived use of QM programs. These ideas assume that if an organization has more completely followed the QM philosophy, QM programs should be used throughout the organization and in various functional areas, rather than in isolation.…”
Section: Quality Management (Qm) Maturitymentioning
confidence: 75%
See 1 more Smart Citation
“…In this study, QM maturity refers, in a qualitative sense, to the degree of QM implementation in an organization. We suggest and previous research has shown (Ahire & Golhar, 1996;Flynn et al, 1994;Fok et al, 2000Patti et al, 2001;Saraph et al, 1989) that it can be measured by examining the perceived use of QM programs. These ideas assume that if an organization has more completely followed the QM philosophy, QM programs should be used throughout the organization and in various functional areas, rather than in isolation.…”
Section: Quality Management (Qm) Maturitymentioning
confidence: 75%
“…If an organization, on the other hand, has very little or no experience with QM, the opposite is expected to occur. In earlier research (Fok et al, 2000;Fok et al, 2001;Patti et al, 2001), we began the process of developing a measure of QM maturity. The instrument we developed dealt with perceived program use and asked respondents whether certain programs were in use in the organization, with a range from not used to high usage.…”
Section: Quality Management (Qm) Maturitymentioning
confidence: 99%
“…The maturity of a quality management program can be interpreted in several ways: Souza & Voss (2001) established that the maturity occurs based on the quality management system implementation and certification years, while Patti et al (2001) and Fok et al (2003) argue that maturity is related to the best used practices and cannot be assessed based only on quantitative aspects. Furthermore, the maturity of quality management can also be measured by the use of a perceived quality and the effectiveness and the process management efficiency (Grandzol & Gershon, 1998;Rosnah et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A maturidade de um Sistema de Gestão da Qualidade pode ser interpretada de formas adversas: Crosby (1979) e Sousa et al (2001) estabeleceram que a maturidade de um SGQ ocorre em função do tempo de implantação e de certificação do SGQ, enquanto Patti et al (2001) e Singh et Smith (2006) defendem que a maturidade está relacionada às melhores práticas utilizadas. Estes últimos autores argumentam que ter um SGQ certificado não garante que uma organização siga completamente os requisitos e as práticas solicitadas por seus clientes.…”
Section: Referencial Teóricounclassified